2022
DOI: 10.1001/jamanetworkopen.2022.16475
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in Nonopioid Pain Medication Prescribing After the Release of the 2016 Guideline for Prescribing Opioids for Chronic Pain

Abstract: This cohort study examines the preguideline and postguideline prescribing rates of nonopioid vs opioid pain medication among individuals with commercial insurance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Treatments for Acute Pain. The contextual evidence review found limited evidence suggesting variability in patient values and preferences regarding treatments for acute pain ( 60 , 61 ), with some evidence of high satisfaction when postoperative pain was managed using an opioid-sparing pathway ( 62 ). Also, there was variability in clinician values and preferences regarding acute pain treatments that were affected by clinical specialty, knowledge regarding effectiveness, and costs; negative attitudes toward acute pain conditions were associated with less likelihood of using or redosing opioids ( 63 – 67 ).…”
Section: Primary Clinical Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatments for Acute Pain. The contextual evidence review found limited evidence suggesting variability in patient values and preferences regarding treatments for acute pain ( 60 , 61 ), with some evidence of high satisfaction when postoperative pain was managed using an opioid-sparing pathway ( 62 ). Also, there was variability in clinician values and preferences regarding acute pain treatments that were affected by clinical specialty, knowledge regarding effectiveness, and costs; negative attitudes toward acute pain conditions were associated with less likelihood of using or redosing opioids ( 63 – 67 ).…”
Section: Primary Clinical Questionsmentioning
confidence: 99%
“…The timing of this release was associated with accelerated decreases in overall opioid prescribing and declines in potentially high-risk prescribing (e.g., high-dosage opioid prescribing and concurrent prescribing of opioid pain medication and benzodiazepines) ( 58 , 59 ). The release of the 2016 CDC Opioid Prescribing Guideline also was temporally associated with modest increases in the prescribing of nonopioid pain medication ( 60 ). Although not the intent of the 2016 CDC Opioid Prescribing Guideline, design and implementation of new laws, regulations, and policies also appeared to reflect its recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, there is a paucity of studies analyzing the trend of opioid usage for CLBP in the advent of CDC guidelines. In a prospective national cohort study Goldstick et al 40 found an increase in non‐opioid medication usage suggesting adoption of concordant care practices among a generalized adult patient population with known or recent opioid exposure. Our report highlights the contrary where opioid therapy, at least for the treatment of CLBP, not only remains as a mainstay of treatment but also is increasing despite the CDC 2016 guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Similar patterns were found when examining specific subpopulations, including those with chronic pain, previous opioid exposure, substance use disorder, anxiety disorder, or mood disorder. 5 These shifts suggest that nonopioid medications replaced opioid medications, but the overall increase in nonopioid prescribing rates was small. On the other hand, claims data analysis cannot account for commonly used over-the-counter medications (eg, nonsteroidal anti-inflammatory drugs and acetaminophen).…”
mentioning
confidence: 99%
“…In particular, the insurance claims data set from this study did not include patients with public insurance (eg, Medicaid) or no insurance, nor were demographic subgroups analyzed. 5 Previous studies found that patients of Black race, with low income, without insurance, and with Medicaid coverage received fewer opioids, nonopioids, and referrals for nonpharmacologic treatment for pain. 7,8 Therefore, a related but unanswered question is whether the 2016 CDC guideline played a role in nonopioid prescribing among historically minoritized populations.…”
mentioning
confidence: 99%